The Relationship Between The Physical Environment of The House and The Incidence of Pneumonia in Children - Korelia, Eka Rosina (Health Notions, 2017)
In 2013, based on data of morbidity cases (data from January to March 2013) in Kediri Health Center, West Lombok, West Nusa Tenggara, URI (Upper Respiratory Tract Infection) was the highest incidence of of ten major diseases most commonly suffered by the community in Kediri Health Center. Based on the register Child Medical Center book in Kediri Health Center on January to March of 2013, patients with URI pneumonia and non Pneumonia on children under five years was 702 children. This study aims to analyze the relationship of physical environmental factors of the house with the incidence of pneumonia on children under five years. This research uses descriptive analytic design with crossectional approach. Data analysis used univariate and bivariate analysis with Chi Square. Obtained the result that the habit of smoking in the house (POR = 5.379); natural ventilation (POR = 22,685), room occupancy density (POR = 13,000), room humidity level (POR = 5,429), floor type (POR = 1.097), wall type (POR = 1.70) with Pneumonia incidence. There was a relationship of smoking habit in the house, natural ventilation, room density, and humidity level, while the type of floor and type of wall have no relation with the occurrence of Pneumonia. As a reference in evaluating the program in the preparation of pneumonia prevention activities plan for children under five years and coordination with related party handling housing improvement.  Keywords: Physical Environment of House, Pneumonia, Children under five years